Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Insights into the Microwave Instruments Onboard the Fengyun 3D Satellite: Data Quality and Assimilation in the Met Office NWP System - Fabien Carminati; Nigel Atkinson; Brett Candy; Qifeng Lu (Advances in Atmospheric Sciences, 2021)
This paper evaluates the microwave instruments onboard the latest Chinese polar-orbiting satellite, Feng-Yun 3D (FY-3D). Comparing three months of observations from the Microwave Temperature Sounder 2 (MWTS-2), the Microwave Humidity Sounder 2 (MWHS-2), and the Microwave Radiation Imager (MWRI) to Met Office short-range forecasts, we characterize the instrumental biases, show how those biases have changed with respect to their predecessors onboard FY-3C, and how they compare to the Advanced Technology Microwave Sounder (ATMS) onboard NOAA-20 and the Global Precipitation Measurement Microwave Imager (GMI). The MWTS-2 global bias is much reduced with respect to its predecessor and compares well to ATMS at equivalent channel frequencies, differing only by 0.36 ± 0.28 K (1σ) on average. A suboptimal averaging of raw digital counts is found to cause an increase in striping noise and an ascending—descending bias. MWHS-2 benefits from a new calibration method improving the 183-GHz humidity channels with respect to its predecessor and biases for these channels are within ± 1.9 K to ATMS. MWRI presents the largest improvements, with reduced global bias and standard deviation with respect to FY-3C; although, spurious, seemingly transient, brightness temperatures have been detected in the observations at 36.5 GHz (vertical polarization). The strong solar-dependent bias that affects the instrument on FY-3C has been reduced to less than 0.2 K on average for FY-3D MWRI. Experiments where radiances from these instruments were assimilated on top of a full global system demonstrated a neutral to positive impact on the forecasts, as well as on the fit to the background of independent instruments.

Assessment and Assimilation of FY-3 Humidity Sounders and Imager in the UK Met Office Global Model - Fabien Carminati; Brett Candy; William Bell; Nigel Atkinson (Advances in Atmospheric Sciences, 2018)

Reconstructing the confluence zone between Laurentide and Cordilleran ice sheets along the Rocky Mountain Foothills, south‐west Alberta - Daniel J. Utting; Nigel Atkinson; Steven Pawley; Stephen J. Livingstone (Journal of Quaternary Science, 2016)
Landform mapping near the Athabasca valley was fundamental to determining whether the Late Wisconsinan Laurentide and Cordilleran Ice Sheets (LIS, CIS) coalesced. In this paper we examine the detailed landform record using new LiDAR digital elevation and hillshade models of the area of confluence and eventual desuturing of these ice sheets. This work reveals an earlier more extensive Cordilleran advance before coalescence with the LIS. When the ice sheets coalesced, the flow pattern was dominated by ice flow along the mountain front, with Cordilleran ice flowing out of major trunk valleys but Laurentide ice flowing into the Foothills up smaller valleys. This flow pattern implies that when the ice sheets coalesced the CIS was already waning, or at least was not at its maximum. Deglaciation was interrupted by several re‐advances, probably related to the destabilizing effect of proglacial lakes along the ice margin.

Flow‐pattern evolution of the Laurentide and Cordilleran ice sheets across west‐central Alberta, Canada: implications for ice sheet growth, retreat and dynamics during the last glacial cycle - Nigel Atkinson; Steven Pawley; Daniel J. Utting (Journal of Quaternary Science, 2016)
This paper presents a reconstruction of the geometry, dynamics and flow pattern of the Laurentide and Cordilleran ice sheets along the Albertan portion of the eastern Canadian Rocky Mountains during the last glaciation. Sediment–landform associations relating to the evolution of these ice sheets document their initial convergence and mutual deflection across west‐central Alberta. The continued advance of Laurentide ice locally displaced Cordilleran ice westward into the Front Ranges, and deflected trunk ice emerging from the Athabasca River valley south‐eastwards along the Foothills. These convergent flow patterns remained major features in the regional geometry of both ice sheets throughout the Last Glacial Maximum. The onset of deglaciation was characterized by the northward retreat of the Laurentide Ice Sheet, which progressively unblocked valleys along the mountain front. The configuration of buttress removal initiated the Lateglacial expansion and sequential drawdown of the eastern Cordilleran Ice Sheet along fast‐flowing outlet glaciers. Subsequent regional retreat of Laurentide and Cordilleran ice was associated with the development of large proglacial lakes which amplified deglaciation by destabilizing the margins of both ice sheets, triggering extensive readvances due to periodic changes in water level associated with the opening and closing of outlets by ice margin fluctuations.

From animal cage to aircraft cabin: an overview of evidence translation in jet lag research - Greg Atkinson; Alan M. Batterham; Nigel Dowdall; Andrew Thompson; Alwin van Drongelen (European Journal of Applied Physiology, 2014)

Reliability of maximal muscle force and voluntary activation as markers of exercise-induced muscle damage - James Peter Morton; Greg Atkinson; Donald PM MacLaren; Nigel Tim Cable; Gareth Gilbert; Caroline Broome; Anne McArdle; Barry Drust (European Journal of Applied Physiology, 2005)